THR USE OF DIFFERENT LEVELS OF SINGLE CELL PROTEIN IN BROILER RATIONS - K. Al-Janabi, A.; A.K. Diab ‎, ‎I.; G.M. Al-Banna‎, A. (The Iraqi Journal of Veterinary Medicine, 1987)
The present work was carried out in poultry experiment farm of Animal Resources Dept.., College of Agric., Baghdad University, Iraq. Five different levels of single cell protein (0, 5, 10, 15, 20%) replaced to soybean meal in the diets of broiler chick and 600 one day old chicks (Hubberd). The birds were randomly distributed among five treatments (two replicate for each treatment.), 60 chicks per replicate. The results showed that. the diet containing 10% single cell protein was the best diet among the other treatments. The average body weight in six weeks old were 1081.5, 1097, 1171, 1095, 332 gr for the treatments used respectively.